Unlegalized activities and practice of political parties to raise funds to support women candidates - Yanjiv, Tuguldur (Studia Philosophiae Et Juris, 2023)
Mongolia is making policy, implementation, and legal reforms aimed at ensuring gender equality at the decision-making level, including increasing the participation and representation of women, however progress is still slow. It is still ranked below the Asian and global average in the Global Gender Cap Index. Therefore, the issue of financing, which is the main factor affecting the participation and representation of women at the decision-making level, is directed to the study of the voluntary initiatives of political parties aimed at female candidates and the ways in which funds are raised. Also, the researcher tried to give a clear understanding and terms in the scope of the study. Эмэгтэй нэр дэвшигчдийг дэмжих хөрөнгө босгоход чиглэсэн улс төрийн намуудын хуульчлагдаагүй арга хэмжээ ба туршлагууд Хураангуй Монгол Улс шийдвэр гаргах түвшинд жендерийн тэгш байдлын хангах, тэр дундаа эмэгтэйчүүдийн оролцоог нэмэгдүүлэхэд чиглэсэн бодлого, хэрэгжилт, хууль эрх зүйн шинэчлэл хийж байгаа ч ахиц дэвшил удаашралтай хэвээр байна. Иймд шийдвэр гаргах түвшинд эмэгтэйчүүдийн оролцоо, төлөөллийг хангахад нөлөөлөх гол хүчин зүйл болох санхүүжилтийн асуудлыг эмэгтэй нэр дэвшигчдэд чиглэсэн улс төрийн намуудын сайн дурын санаачилга, хөрөнгө босгож байгаа арга замуудыг судлахад чиглүүлсэн болно. Мөн судлагдахууны хүрээнд суурь ойлголтуудыг тодруулахыг хичээлээ. Tүлхүүр үгс: эмэгтэй нэр дэвшигч, улс